STUDI KASUS: KETERLAMBATAN BICARA & KESULITAN PENGUCAPAN LISAN PADA ANAK USIA 6 TAHUN - Adinda Fadillah; Venna Marshaulina Sihombing; Syakilah Kurnia Fahmi Panggabean (LPPM Universitas Ekasakti, 2024)
This case study discusses the factors that led to the speech delay of Kendrick Veriel Surbakti, a six-year-old child, and his spoken language. This case study uses a qualitative method with the type of intrinsic case studies by understanding individual problems. This case study observes in depth by means of direct observation and interviews of the informants concerned. The results showed that the factors of Kendrick's speech and oral language delay included the condition of the family environment, social and cultural environment, lack of verbal stimulation in the surrounding environment as well as shyness to talk to others and the use of gadgets. And from the results of the case study that has been conducted, Kendrick is only able to pronounce 2 to 4 words consecutively and the pronunciation of consonant letters is less precise when speaking.